2004
DOI: 10.1002/aoc.655
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of exogenous and endogenous selenium to bile after the intravenous administration of environmentally relevant doses of arsenite to rabbits

Abstract: Extending our studies of the effect of arsenite on the metabolism of inorganic selenium (selenite and selenate) to lower doses, we intravenously injected New Zealand white rabbits with aqueous solutions of arsenite, selenite, arsenite + selenite, selenate and selenate + arsenite at 50 µg and 5 µg metalloid per kilogram body weight. Bile samples were collected for 25 min, acid-digested and analyzed for total arsenic and selenium by double focusing magnetic sector field inductively coupled plasma mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Evidence directly supporting the aforementioned claim was provided by studies performed on rabbits showing a mobilization of Se to the liver and bile following exposure to arsenic 470. The proposed antagonistic relationship between As and Se, where one modifies the toxic effects induced by the other,471 prompted Berry and co-workers to directly analyze their interaction at the sub-cellular level in rat kidney cells using EPXMA combined TEM 472.…”
Section: Microprobe X-ray Fluorescence Imaging Techniquesmentioning
confidence: 96%
“…Evidence directly supporting the aforementioned claim was provided by studies performed on rabbits showing a mobilization of Se to the liver and bile following exposure to arsenic 470. The proposed antagonistic relationship between As and Se, where one modifies the toxic effects induced by the other,471 prompted Berry and co-workers to directly analyze their interaction at the sub-cellular level in rat kidney cells using EPXMA combined TEM 472.…”
Section: Microprobe X-ray Fluorescence Imaging Techniquesmentioning
confidence: 96%
“…At the simplest level, it suggests that the chronic dietary ingestion of arsenite (e.g. through drinking water) will likely deplete the body of selenium [16,17] and render ingested selenium physiologically unavailable through coordination to arsenic in the blood. Since selenium is an essential nutrient, with a well-known protective activity against at least some cancers [18], this may help to explain the long known carcinogenicity of inorganic arsenic in humans [19].…”
Section: Selenium and Heavy Metal Poisoningmentioning
confidence: 99%
“…In principle, the toxicity of any metal species may be attributed to interactions with endogenous target ligands that occur either in the bloodstream [70] {in case of a gastrointestinally absorbed metal, one must also consider metal-amino acid complexes, since these may be the species that are absorbed into the bloodstream [71]; with regard to the metal-based drugs cis-platin (Figure 1 appreciably interact with endogenous ligands [53]} and/or within organs [72,73]. It is also important to note that the biological response of an organism to any given metal species is dose-dependent ("the dose makes the poison") and that a different set of endogenous ligands appear to be targeted in acute [74] as opposed to chronic As III toxicity [64]. Blood plasma alone may contain up to 10,000 potential protein ligands [75].…”
Section: Interaction Of Absorbed/injected Metal Species With Endogenomentioning
confidence: 99%
“…Considering that free selenite has been detected in human blood plasma [154], this intriguing trace element antagonism was hypothesized to be implicated in the chronic toxicity of As(OH) 3 . Investigations aimed at uncovering its biomolecular basis revealed that it appeared to be based on the rapid in vivo assembly of the seleno-bis(S-glutathionyl) arsinium ion, (GS) 2 AsSe − (Figure 1(d)) in the bloodstream (in erythrocytes [91]) followed by its translocation to the plasma, the liver and its eventual excretion in bile [62,64]. Since the structure of this species was entirely derived from EXAFS and Raman spectroscopy, its unequivocal confirmation required an alternative technique.…”
Section: Interaction Of Two or Three Toxic Metals With One Endogenousmentioning
confidence: 99%
See 1 more Smart Citation